2022
DOI: 10.3329/jujbs.v10i1-2.60848
|View full text |Cite
|
Sign up to set email alerts
|

Breeding ecology of the Asian pied starling (Gracupica contra) at Jahangirnagar University campus, Bangladesh

Abstract: The breeding ecology of the Asian pied starling (Gracupica contra) was studied between 2015 and 2016 at Jahangirnagar University (JU) campus to document the breeding period, nests and nest-site selection, clutch size, egg morphology, hatching and breeding success. Breeding activities of starling in JU campus started in late February and continued to early September. A total of 105 nests were recorded in two breeding seasons. The nests were loosely constructed out of straw into the shape of a dome with an entra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our study, more than 50% of total nest cavities were found in three species of trees (Swietenia mahagoni, Abizia procera and Samania saman) of > 42 cm in DBH. Earlier studies also showed that these trees are commonly found at JU campus and provide nesting resources to a wide variety of birds including cavity nesters (Jahan et al 2018;Shoma & Begum, 2020;Shoma, 2021).…”
Section: Fig 2 Distance Of Nesting Trees From Nearby Roadsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, more than 50% of total nest cavities were found in three species of trees (Swietenia mahagoni, Abizia procera and Samania saman) of > 42 cm in DBH. Earlier studies also showed that these trees are commonly found at JU campus and provide nesting resources to a wide variety of birds including cavity nesters (Jahan et al 2018;Shoma & Begum, 2020;Shoma, 2021).…”
Section: Fig 2 Distance Of Nesting Trees From Nearby Roadsmentioning
confidence: 99%
“…Jahangirnagar university campus is home to about 195 species of birds which comprises about 30% of the total bird species in Bangladesh (Begum, 2016). The diverse habitat features made the campus an attractive nesting and roosting ground for a broad range of bird communities including several species of primary and secondary cavity-nesting birds (Mohsanin & Khan, 2009;Rahman et al, 2019;Shoma & Begum, 2020;Shoma, 2021). However, habitat fragmentation and continuous loss of trees due to growing infrastructure developments may threaten the reproduction and survival of cavity-nesting birds in the campus.…”
Section: Introductionmentioning
confidence: 99%